Shareholder-Creditor Conflict and Payout Policy: Evidence from Mergers between Lenders and Shareholders - Chu, Yongqiang (Review of Financial Studies, 2018)
This paper studies how the conflict of interest between shareholders and creditors affects corporate payout policy. Using mergers between lenders and equity holders of the same firm as shocks to the shareholder-creditor conflict, I find that firms pay out less when there is less conflict between shareholders and creditors, suggesting that the shareholder-creditor conflict induces firms to pay out more at the expense of creditors. The effect is stronger for firms in financial distress. Received March 22, 2017; editorial decision October 17, 2017 by Editor Wei Jiang. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web Site next to the link to the final published paper online.